NILAI INTERAKSI VISUAL DALAM PERKEMBANGAN MEDIUM KOMUNIKASI PADA ERA REVOLUSI INDUSTRI 4.0 - Larry Julianto, I Nyoman (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2019)
Visual Communication Design is a science that until now has always been coupled with technological developments and visual culture. Technological developments are triggered by the development of the ‘way of thinking’ of society, so that the interaction value of a visual communication medium develops in the stimulus aspect in producing a response. The development of media as a medium of communication resulted in difficulties in understanding the logic of design thinking in defining the definition of media, the science of the design, and scope of its design. The development of the communication medium in the era of industrial revolution 4.0 makes conventional and digital visual media increasingly questionable about how the process of communicating their message. A visual communication media has effective and communicative benchmarks in an effort to produce a response after going through the 'organism' stage, so it needs to be understood and examined together to reinforce the definition and scope of its design. The development of media in a medium of visual communication in the era of industrial revolution 4.0, produces a ‘feed back’ that refers to changes in lifestyle and audience interaction that leads to the phenomenon of disruptive innovation. The definition of media experiences refraction due to the ‘disruption effect’ caused by the development of visual interaction process to improve the ‘emotional design’. The value of interaction which is born from the ability of ‘way of life’ creates new value dimensions that cannot be constructed from the previous media, so that the development of ‘paperless’ media will become an 'up-to-date' interaction medium in the spirit of industrial revolution 4.0.